Social Lives of Monumental Walls: Hunting along the Upper Tigris. (3rd April 2021) - Sconzo, Paola; Simi, Francesca; Ahmadpour, Amir
ABSTRACT: On the left bank of the Tigris in northern Iraq, in an area today partially flooded by the Mosul Dam reservoir, lies an enigmatic monumental enclosure known in the literature as the "Tigris Wall." Before its partial submersion under the waters of the modern lake, the large L-shaped embankment, about 4 × 4 km long, enclosed an area of ca. 1600 ha, overlooking the Tigris and its alluvial plain. By means of a holistic strategy that includes different levels of analysis (remote sensing, pedestrian and UAV photogrammetric surveys, excavation, and settlement pattern analysis), this paper addresses the structure, its context, and its environment. Relying on the results of this multi-disciplinary approach, we present an updated and detailed discussion of the structure's possible functions and interpretations. Parallels from northern Mesopotamia and neighboring regions are used to suggest that the Tigris Wall may be the first archaeologically known hunting park in the region, probably dating to the Late Sasanian or Early Islamic epoch.